Understanding purchase intention for different personality traits in social networking services / Azrin Ali - Ali, Azrin (2021)
What prompts users to readably purchase online compared to others is a beneficial insight for successful marketing campaigns. Purchase intention forecasts actual purchase act thus is desirable to be scrutinised. Furthermore, in social networking services settings, ample factors surface to observe purchase intentions from the user’s standpoint. While there are many facets to an individual makeup, understanding personality traits could be an excellent interplay in explaining purchase intention. The Big Five Factor Model (BFM) is utilised to predict the effect of personality traits in the aspect of business, specifically in the angle of purchase intention in social networking services (SNS). Personality traits (N=133) from the Big Five Model were found to be significant for SNS users’ using multiple regression analysis. Descriptive analyses were included to interpret the data. The value of this study showed that as a group, personality traits were significant on purchase intention, and proved that different versions of a similar message could be churned in a campaign to maximise conversion. The findings can fine-tune marketers’ way of handling different types of messages conveyed in SNS, and this research empirically investigated different personality types drawing from Big Five Model to understand purchase intention in SNS.